A study of sodar observed shear echo structures in relation to wind velocity and other turbulence parameters - SINGAL, SP; GERA, BS; PAHWA, DR; AGGARWAL, SK (MAUSAM, 1987)
The various types of sodar structures observed on land during nocturnal stable conditions have been studied in relation to the changes in meteorological parameters of surface wind speed, frictional velocity and Richardson’s number. The data for the period May 1977 to April 1982 have been used for these studies. It has been found that surface winds contribute to the tall spiky surface based layer structures while the behavior of the frictional velocity and Richardson's number give information about the formation and break up of the eddies in the stable layers of height upto 100m and more respectively.